THE LEVEL OF SELF-DIRECTED LEARNING READINESS OF 2013 ACADEMIC YEAR’S STUDENT AT ENGLISH DEPARTMENT OF THE STATE UNIVERSITY OF PADANG - Yuri Hardianti; Refnaldi refnaldi; An Fauzia Rozani Syafei (Universitas Negeri Padang, 2016)
This research discusses about students’ level of self-directed learning readiness in learning English. The subject of the research is English students class of 2013 which selected by using simple random sampling method. The identified problem of the study is how the students SDLR level influences their learning English strategy. The objective of the study is to discover students’ SDLR level and factors that influence their low level SDLR in learning English. There were two instruments used on the research, the questionnaire and a semi-structured interview. The result showed that the students had below average level of SDLR with an average score of 189.68. Based on the interviewed administered to the 16 students who scored below average level of SDLR, factors that influenced their low SDLR score were self-concept as an effective and independent learner, creativity and initiative in learning. In conclusion, English department students of UNP has low self-directed learning readiness level, and self-concept as an effective and independent learner, creativity and initiative in learning are its cause factors.